2021
DOI: 10.1371/journal.pone.0247055
|View full text |Cite
|
Sign up to set email alerts
|

Statistical meta-analysis to investigate the association between the Interleukin-6 (IL-6) gene polymorphisms and cancer risk

Abstract: A good number of genome-wide association studies (GWAS), including meta-analyses, reported that single nucleotide polymorphisms (SNPs) of the IL-6 gene are significantly associated with various types of cancer risks, though some other studies reported insignificant association with cancers, in the literature. These contradictory results may be due to variations in sample sizes and/or deficiency of statistical modeling. Therefore, an attempt is made to provide a more comprehensive understanding of the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 130 publications
(34 reference statements)
2
16
0
Order By: Relevance
“…For IL-10 (-592 C>A), comparison of genotype frequencies between CRC cases and healthy controls showed that carriers of the C/A genotype were negatively associated with CRC occurrence. This was consistent with the meta-analysis conducted in a Chinese population where it was stated that this variant was associated with a significantly reduced CRC risk [31]; similar findings were reported in an ethnic Kashmiri population where the carriers of the minor allele A were associated with a reduced CRC risk [40]. Conversely, two meta-analyses found no correlation [24,41].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For IL-10 (-592 C>A), comparison of genotype frequencies between CRC cases and healthy controls showed that carriers of the C/A genotype were negatively associated with CRC occurrence. This was consistent with the meta-analysis conducted in a Chinese population where it was stated that this variant was associated with a significantly reduced CRC risk [31]; similar findings were reported in an ethnic Kashmiri population where the carriers of the minor allele A were associated with a reduced CRC risk [40]. Conversely, two meta-analyses found no correlation [24,41].…”
Section: Discussionsupporting
confidence: 90%
“…In this context, the pro-and anti-inflammatory interleukins IL-1β, IL-6 and IL-10 are the most involved in the development of these neoplasms and are activated by various signaling pathways during CRC progression, supporting their crucial role in pathogenesis [7,12,13]. In this regard, several studies have reported the association of different interleukin gene polymorphisms, particularly those involved in modulating cytokine expression, such as IL-1β (-31C>T), IL-6 (-174G>C) and IL-10 (-592C>A) variants with CRC risk [24,[29][30][31][32]. However, to date there have been only a few studies focusing on CRLM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a consensus decision about the association of HIF1A gene polymorphisms with multiple disease risk is required to make a treatment plan against this genetic effect. To make a consensus decision about the contradictory findings of different studies more accurately, researchers usually consider statistical meta-analysis [ 15 , 55 60 ]. The meta-analysis makes a decision about the association more accurately compared to SGA studies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent data support the role of several SNPs in IL-6 (Interleukin 6) gene (rs1800795, rs1800796 and rs1800797) as biomarkers of an increased cancer risk in several tumors. Specially, variants rs1800795 and rs1800796 are associated with an overall increased risk of PC ( Harun-Or-Roshid et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%